2021
DOI: 10.1002/fsn3.2599
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solid state fermentation on proximate composition, antinutritional factors and in vitro protein digestibility of maize flour

Abstract: Cereals including maize generally have limiting amino acids particularly lysine. In most cases, spontaneous fermentation is used to improve the nutritional profiles of maizebased products. However, in such fermentation, biological risks including the presence of pathogenic microorganisms, chemical contaminants, and toxic compounds of microbial origin such as mycotoxins pose a health risk. The aim of this study was, therefore, to improve the nutritional properties of maize flour by reducing antinutritional fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Ge et al (2021) explored the interaction of tea polyphenols with soy milk proteins on soybean trypsin inhibitors and showed that the addition of tea polyphenols not only changed the conformation of soy milk proteins, but also presumably reduced the activity of soybean trypsin inhibitors by altering the hydrophobic interaction and hydrogen bonding of proteins in soy milk. Terefe et al (2021) used the microbial fermentation of Lactobacillus plantarum and Saccharomyces cerevisiae strains and their co‐cultures to reduce antinutritional factors, thereby improving the nutritional properties of corn flour. The results indicated that this strain and its co‐cultures were found to be useful for corn flour fermentation, the activity of trypsin inhibitor in corn meal is significantly reduced, which is more effective than traditional fermentation process.…”
Section: Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge et al (2021) explored the interaction of tea polyphenols with soy milk proteins on soybean trypsin inhibitors and showed that the addition of tea polyphenols not only changed the conformation of soy milk proteins, but also presumably reduced the activity of soybean trypsin inhibitors by altering the hydrophobic interaction and hydrogen bonding of proteins in soy milk. Terefe et al (2021) used the microbial fermentation of Lactobacillus plantarum and Saccharomyces cerevisiae strains and their co‐cultures to reduce antinutritional factors, thereby improving the nutritional properties of corn flour. The results indicated that this strain and its co‐cultures were found to be useful for corn flour fermentation, the activity of trypsin inhibitor in corn meal is significantly reduced, which is more effective than traditional fermentation process.…”
Section: Passivationmentioning
confidence: 99%
“…Yao et al (2021) used Bacillus subtilis to reduce antinutritional factors in soybean meal significantly reduced antinutritional factors such as trypsin inhibitor, urease, and phytate. Terefe et al (2021) used Lactobacillus plantarum , Saccharomyces cerevisiae , and their co‐cultures to microbial fermentation of corn flour, which increased protein content and digestibility, and reduced phytic acid, tannin, and trypsin inhibitory activities. Some scholars investigated that the activity of antinutritional factors such as phytic acid, saponins, tannins, and LOX were significantly reduced and protein digestibility, bioactive components, and related antioxidant capacity were significantly changed after co‐fermentation treatment of foxtail millet and defatted rice bran, respectively (Sharma & Sharma, 2022; Su et al, 2022).…”
Section: Passivationmentioning
confidence: 99%
“…Corn is one of the main grains produced worldwide, providing 30% of food calories for more than 4.5 billion people worldwide, and is considered to be the main staple food in most countries ( 1 , 2 ). Whereas, compared with other cereal crops, the nutritional value of corn is low, lacking essential amino acids and lysine ( 3 ). Soy-derived foods have been consumed for centuries, especially in Asian diets.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of the changes in the protein digestibility after SSF with Rhizopus sp. are mixed in the literature 39,40 , and could be affected by the phenolic content of PRG and the changes in the free amino acid content of the substrate after SSF.…”
Section: Chemical Composition Analysismentioning
confidence: 99%